Analisis Sosiolinguistik Penggunaan Kata Serapan Bahasa Asing dalam Komunikasi Daring di Kalangan Remaja Indonesia - Nur Indah Sari; Eka Septiani (Lembaga Yasin AlSys, 2025)
The phenomenon of foreign loanword usage in online communication among Indonesian adolescents reflects linguistic dynamics shaped by globalization and the advancement of digital technology. As active users of social media, adolescents exhibit a tendency to adopt foreign vocabulary, both consciously and unconsciously as a means of expressing identity, lifestyle, and the influence of popular culture. This study aims to analyze the forms, functions, and sociolinguistic factors underlying the use of foreign loanwords in Indonesian adolescents' online communication. A descriptive qualitative method with a sociolinguistic approach was employed. Data were collected through netnographic observation on social media platforms, documentation of online communication screenshots, and semi-structured interviews with adolescent social media users. The findings reveal that words such as literally, cringe, vibes, and FYI are used not only as adaptations to global trends but also serve as markers of social group identity and linguistic style perceived as modern and inclusive. The study concludes that the use of foreign loanwords in online communication signifies a shift in language norms among adolescents, influenced by social, cultural, and technological factors. The implications of this study highlight the need for Indonesian language education in schools to accommodate such phenomena within the framework of digital literacy and the development of critical language awareness in the global era.